2014
DOI: 10.1007/s13277-014-1899-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of CD117 in differential diagnosis of acute leukemias

Abstract: C-kit receptor (CD117) and its ligand, stem cell factor, play a key role in normal hematopoiesis. It has been demonstrated that its expression extremely increases in leukemias with myeloid commitment. We analyzed findings on CD117 expression together with other myeloid related markers in 203 de novo acute leukemias, referred to Iranian immunophenotyping centers: Iranian Blood Transfusion Organization (IBTO) and Baghiatallah Hospital (BH). All cases were characterized based on the French American British cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…18 Present study showed a higher number of cases showing CD117 positivity (86.56%) in comparison to the study conducted by Ahmadi et al, where CD117 positivity was seen in 75 % of AML with none of the cases of ALL showing positivity for this marker. 19 Also in their study CD117 was positive in 100 % of M5a cases with no M5b cases being positive for this marker. Present study also showed a higher number of cases with CD117 positivity in comparison to the study conducted by Auewarakul CU et al, where out of 163 AML cases, 67% expressed CD117.…”
Section: Discussionmentioning
confidence: 85%
“…18 Present study showed a higher number of cases showing CD117 positivity (86.56%) in comparison to the study conducted by Ahmadi et al, where CD117 positivity was seen in 75 % of AML with none of the cases of ALL showing positivity for this marker. 19 Also in their study CD117 was positive in 100 % of M5a cases with no M5b cases being positive for this marker. Present study also showed a higher number of cases with CD117 positivity in comparison to the study conducted by Auewarakul CU et al, where out of 163 AML cases, 67% expressed CD117.…”
Section: Discussionmentioning
confidence: 85%
“…The protein expression assessment was performed by scoring based on the percentage of stained cells and the intensity of nuclear stain, according to the method described previously. 22 - 24 …”
Section: Methodsmentioning
confidence: 99%
“… 53 developed a DNA aptamer specifically targeting CD117, a biomarker highly expressed by certain AML cells. 54 , 55 For the therapeutic study, the aptamer was conjugated with methotrexate (MTX) to generate Apt-MTX conjugates. This Apt-MTX conjugate showed significantly enhanced inhibition of cellular growth, triggered cell apoptosis, and induced G1 phase cell-cycle arrest of the AML cell line HEL and primary AML cells from patients, compared to MTX treatment alone, with negligible toxicity on off-target cells.…”
Section: Main Textmentioning
confidence: 99%